2017
DOI: 10.1017/s0142716417000522
|View full text |Cite
|
Sign up to set email alerts
|

Development of early morphological awareness in Greek: Epilinguistic versus metalinguistic and inflectional versus derivational awareness

Abstract: This cross-sectional study examined the development of morphological awareness in Greek children 4–7 years old. A distinction was adopted between epilinguistic control, evidenced in judgment tasks and indicative of elementary levels of awareness, and metalinguistic awareness, evidenced in production tasks and indicative of full-blown conscious awareness. The morphological domains of inflectional and derivational morphology were specifically contrasted to determine whether they follow distinct developmental tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 66 publications
(78 reference statements)
1
34
0
2
Order By: Relevance
“…In contrast, metalinguistic awareness refers to the individual’s ability to reflect upon and consciously manipulate morphemes, as well as the ability to deliberately apply word formation rules. Following Carlisle (1995), epilinguistic control is evidenced in judgment tasks, whereas full-blown metalinguistic awareness is evidenced in production tasks (see Diamanti et al, in press, for further discussion). In addition to the expected performance increase with age, Diamanti et al (in press) found that a single factor sufficed and accounted for 0.59 of the variance in the four tasks, consistent with a common developmental path underlying both domains and both levels of morphological awareness.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In contrast, metalinguistic awareness refers to the individual’s ability to reflect upon and consciously manipulate morphemes, as well as the ability to deliberately apply word formation rules. Following Carlisle (1995), epilinguistic control is evidenced in judgment tasks, whereas full-blown metalinguistic awareness is evidenced in production tasks (see Diamanti et al, in press, for further discussion). In addition to the expected performance increase with age, Diamanti et al (in press) found that a single factor sufficed and accounted for 0.59 of the variance in the four tasks, consistent with a common developmental path underlying both domains and both levels of morphological awareness.…”
Section: Introductionmentioning
confidence: 95%
“…Following Carlisle (1995), epilinguistic control is evidenced in judgment tasks, whereas full-blown metalinguistic awareness is evidenced in production tasks (see Diamanti et al, in press, for further discussion). In addition to the expected performance increase with age, Diamanti et al (in press) found that a single factor sufficed and accounted for 0.59 of the variance in the four tasks, consistent with a common developmental path underlying both domains and both levels of morphological awareness. In comparison of the developmental growth curves among tasks, they found that production of derivational morphemes was more difficult than production of inflectional morphemes and judgment of derivational morphemes, whereas the differences between the two inflectional tasks and between the two judgment tasks were not significant.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations